Analysis of the Role of the Mc4r System in Development, Growth, and Puberty of Medaka - Liu, Ruiqi; Kinoshita, Masato; Adolfi, Mateus C.; Schartl, Manfred (Frontiers in Endocrinology, 2019)
In mammals the melanocortin 4 receptor (Mc4r) signaling system has been mainly associated with the regulation of appetite and energy homeostasis. In fish of the genus Xiphophorus (platyfish and swordtails) puberty onset is genetically determined by a single locus, which encodes the mc4r. Wild populations of Xiphophorus are polymorphic for early and late-maturing individuals. Copy number variation of different mc4r alleles is responsible for the difference in puberty onset. To answer whether this is a special adaptation of the Mc4r signaling system in the lineage of Xiphophorus or a more widely conserved mechanism in teleosts, we studied the role of Mc4r in reproductive biology of medaka (Oryzias latipes), a close relative to Xiphophorus and a well-established model to study gonadal development. To understand the potential role of Mc4r in medaka, we characterized the major features of the Mc4r signaling system (mc4r, mrap2, pomc, agrp1). In medaka, all these genes are expressed before hatching. In adults, they are mainly expressed in the brain. The transcript of the receptor accessory protein mrap2 co-localizes with mc4r in the hypothalamus in adult brains indicating a conserved function of modulating Mc4r signaling. Comparing growth and puberty between wild-type and mc4r knockout medaka revealed that absence of Mc4r does not change puberty timing but significantly delays hatching. Embryonic development of knockout animals is retarded compared to wild-types. In conclusion, the Mc4r system in medaka is involved in regulation of growth rather than puberty.